Identification of criticalwatershed pakerisan based on remote sensing and geographic information systems for sustainable land capability - Supriatna, Ade; Sumantra, I.K; Ariati, Putu Eka Pasmidi (Economic Military and Geographically Business Review, 2023)
Watersheds can be viewed as natural systems where complex hydrological biophysical processes as well as socio-economic and cultural activities of the community take place. Changes in watershed hydrological conditions as a result of uncontrolled expansion of cultivation areas without regard to soil and water conservation principles often lead to conditions of increased erosion and sedimentation, decreased land productivity, and accelerated land degradation. The purpose of this research was to determine the level of erosion’s danger and critical level of land in the watershed Pakerisan. Determination of the critical level of land is done by evaluating the parameter determining critical areas, such as the closure and land productivity, slope, erosion, and land management with the scoring method. The level of erosion’s danger is calculated using the Universal Soil Loss Equation (USLE). The results shows that the level of the erosion’s danger in the watershed Pakerisan is very light of 38 covering 4654.69 ha (51.19%), light as many as 44 units of land area of 3243.54 (35.68% ), medium 15 units of land area of 1022.29 ha (11.24%) and weight 3 units of land area of 171.97 ha (1.89%). Critical level of land area in Watershed Pakerisan consists of a non-critical area of 5653.99 ha (62.19%), potential critical area of 1951.67 ha (21.47%) and rather critical area of 1486.23 ha (16.35% ). Avoid further escalation of the critical level of land in the watershed Pakerisan, the real efforts of stakeholders including government, private, and community is needed